Two Mutations in Exon XII of the Protein Sα Gene in Four Thrombophilic Families Resulting in Premature Stop Codons and Depressed Levels of Mutated mRNA - Andersen, Bente Damm; Lind, Bent; Philips, Malou; Hansen, Annebirthe Bo; Ingerslev, Jørgen; Thorsen, Sixtus (Thrombosis and Haemostasis, 1996)
Sixteen Danish unrelated thrombophilic families with plasma protein S deficiency of type I (or III) are currently under investigation in our laboratory for defects in the protein Sα gene. The present paper describes a part of this work, which deals with the identification and phenotypical presentation of two unique mutations in exon XII of the protein Sa gene in four of these families. The mutations were identified by SSCP screening followed by nucleotide sequence analysis or by direct nucleotide sequence analysis. The mutation found in one family (D) is a novel deletion of an A in either the codon for Gly448 (GGA) or Iie449 (ATT) resulting in a frameshift and a premature stop codon at position 454. The other mutation shared by three families (F, G and J) is a previously reported C → T transition within a hypermutable CG dinucleotide sequence converting Arg410 (CGA) to Stop (1GA). All affected individuals are heterozygotes for their mutation and in each family the protein S genotype, the plasma protein S phenotype (not shown for Family J) and the clinical phenotype cosegregate. The two mutations can fully explain the abnormal protein S phenotype since premature stop codons are known to disrupt gene function of the mutated allele. Analysis of protein S mRNA from platelets showed that both mutations result in a marked reduction in the amount of protein S mRNA from the mutated alleles indicating that the mutations exert their deleterious effects on gene expression at the transcriptional level. The Arg410 → Stop mutation in Families F, G and J is in all instances linked to a G at the site of a common neutral dimorphism in the codon for Pro626 (CCA/G) in exon XV. This indicates that the mutation in these families could have arisen in a common ancestor. The Arg410 (CGA) → Stop (1GA) mutation is also seen in exon XII of the normal protein Sa gene. This gives rise to the speculation as to whether the mutation in the protein Sa gene is the result of an interaction with the protein Sβ gene leading to double homologous unequal crossing-over or gene conversion of a short DNA sequence. However, this is unlikely since none of the 7 other protein S β-specific nucleotides are present in the mutated exon XII sequence of the protein Sα gene. The common Arg506 → Gin Leiden mutation in coagulation factor V is not an additional risk factor for thrombosis in any of the four families studied.